Kinetika Reaksi Deproteinasi Limbah Udang Ebi Pada Isolasi Kitin - Ridho Wijaya; Ahmad Fadli; Idral Amri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Chitin is a biopolymer and can be synthesized from ebi shrimp waste through deproteination and demineralization processes. The purpose of this study was to determine the kinetics of deproteination reaction in chitin isolate with variable reaction temperature and stirring rate. The study began by reacting shrimp waste powder with 3.5% NaOH solution using a ratio of 1:10 at 75 ° C, 85 ° C and 95 ° C and 200 stirring speeds, and 250 rpm in a glass beaker equipped with stirrer. Samples were taken every 10, 20, 30, 50, 70, 90, 110 and 120 minutes as much as 40 mL, then washed until the pH was neutral and the sample filtered. The shrimp powder produced was analyzed using titration method of formol to know the protein content contained in the sample. The results showed that the reaction kinetics follows the pseudo first order equation. The higher the temperature and the speed of stirring given to the deproteination process the greater the concentration produced. The reaction speed constant at 75°C, 85°C and 95°C with 200 rpm stirring speed was obtained at k = 0.0098 min-1 to 0.0217 min-1. While at 250 rpm stirring speed k = 0.0113 min-1 to 0.0255 min-1. The optimal condition available in this study is 95oC with 250 rpm stirring speed so that it produces protein from 14.08% to 0.87%.Key words : Deproteination, chitin, reaction kinetics, ebi shrimp waste, FTIR analysis.